Influence of muscle mass and bone mass on the mobility of elderly women: an observational study - Falsarella, Gláucia R (BioMed Central, 2014)
BACKGROUND: The purpose of this study was to investigate the influence of muscle mass and bone mineral density on markers of mobility in dwelling elderly women. METHODS: This cross-sectional study included 99 elderly women, who were 65 years old or above, in Campinas-SP, Brazil. To collect data, we used sociodemographic data, the body mass index (BMI), health status, comorbidities, use of medications, mobility tests (TUG and gait speed) and examinations of the body composition (densitometry with dual-emission X-ray absorptiometry “DXA”). In order to examine the relationship between muscle and bone mass with mobility (gait speed and TUG), we applied the Spearman correlation coefficient. Also was applied the analysis of covariance (ANCOVA) adjusted for age and comorbidities. To identify the factors associated with mobility, we used the univariate and multivariate logistic regression analysis. The level of significance for statistical tests was P < 0.05. RESULTS: The correlation between sarcopenia and bone mineral density with mobility tests showed a significant relationship only between sarcopenia and TUG (r = 0.277, P = 0.006) in Spearman correlation coefficient. The result of the correlation analysis (ANCOVA) showed that sarcopenia was associated with gait speed (r(2) = 0.0636, P = 0.0018) and TUG (r(2) = 0.0898, P = 0.0027). The results of the multivariate analysis showed that age (P = 0.034, OR = 1.081) was associated with worse performance on gait speed. By highlighting the TUG test, the results of the multivariate analysis showed that the age (P = 0.004, OR = 1.111) and BMI in overweight (P = 0.011, OR = 7.83) and obese (P < 0.001, OR = 7.84) women were associated with lower performance of the functionality of the lower limbs. CONCLUSION: The findings with regard to mobility tests which were analyzed in this study indicate the association of variables related to the aging process that contribute to the decline in physical performance, for example, age, BMI and sarcopenia.